2014
DOI: 10.1007/jhep11(2014)117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of LSP character on Slepton reach at the LHC

Abstract: Searches for supersymmetry at the Large Hadron Collider (LHC) have significantly constrained the parameter space associated with colored superpartners, whereas the constraints on color-singlet superpartners are considerably less severe. In this study, we investigate the dependence of slepton decay branching fractions on the nature of the lightest supersymmetric particle (LSP). In particular, in the Higgsino-like LSP scenarios, both decay branching fractions of˜ L andν depend strongly on the sign and value of M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 54 publications
3
34
0
Order By: Relevance
“…Since dedicated DM searches through direct detection are not sensitive to our scenario, the 14 TeV LHC will be the most important experiment to probe it. We expect that the reach for dark muons should be improved by close to a factor of two during run II, similarly to what was found for smuons [60,61]. Thus, the parameter space of the heavy lepton scenario will be fully covered, since the g µ − 2 anomaly sets an upper bound m L 800 GeV for couplings y < 4π.…”
Section: Discussionsupporting
confidence: 56%
“…Since dedicated DM searches through direct detection are not sensitive to our scenario, the 14 TeV LHC will be the most important experiment to probe it. We expect that the reach for dark muons should be improved by close to a factor of two during run II, similarly to what was found for smuons [60,61]. Thus, the parameter space of the heavy lepton scenario will be fully covered, since the g µ − 2 anomaly sets an upper bound m L 800 GeV for couplings y < 4π.…”
Section: Discussionsupporting
confidence: 56%
“…[26] has established a 95% CL exclusion limit of 550 GeV with Mχ0 To be consistent with the rest of the paper we have extracted the background yield of Ref. [26] and extrapolated the 95% CL exclusion limit for sleptons at 3000 fb −1 , with our definition of statistical significance. We found the corresponding limits to be ∼ 775 GeV forl L and ∼ 670 GeV forl R with Mχ0 1 = 100 GeV.…”
Section: Sleptonsmentioning
confidence: 62%
“…Although we did not carry out any exclusive search for smuons, whenever necessary we have extrapolated the results from Ref. [26], where the authors have explored the prospect of finding sleptons at the LHC for different compositions of the LSP.…”
Section: Parameter Space and General Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Slepton decays would follow a similar trajectory. In fact this scenario was studied in reference [33] and found that unless the spectrum was quite compressed, left handed slepton mass bounds might be set as high as 490 GeV. This is because over much of parameter space charged sleptons prefer to decay to a lepton and lightest neutralino, rather than a neutrino and chargino.…”
Section: Higgsino Nlspmentioning
confidence: 99%